Beyond the lean start-up: experimentation in corporate entrepreneurship and innovation. Issue 1 (2nd January 2020) - Hampel, Christian; Perkmann, Markus; Phillips, Nelson
ABSTRACT: In this essay, we argue that entrepreneurship and innovation researchers should pay more attention to experimentation as an approach to innovation and corporate entrepreneurship in established firms. While there is a growing body of research examining experimentation in start-ups, there is no corresponding literature investigating the role of experiments in the innovation and corporate entrepreneurship activities of established firms despite the increasing interest in experimentation among managers and the growing practitioner literature urging established firms to adopt experimentation. We discuss this trend and point to a number of research areas that we believe deserve systematic research.